Kirjoja koulutuksen ja työelämän yhteistyöstä sekä työssä oppimisesta - Collin, Kaija; Tynjälä, Päivi (Aikuiskasvatus, 2000)
The developmental challenges in the cooperation of education and training and working life, Pekka Ruohotie, Juhani Honka & Antti Suvanto (toim.), Helsinki (1999)
Keywords: kirja-arvostelut; työssäoppiminen; Work-based learning : prospects and challenges; The developmental challenges in the cooperation of education and training and working life